Online Google Book Sebagai Perpustakaan Digital Alternative Masa Depan - Jamridafrizal Jamridafrizal (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
Google Books, as one of the facilities provided by Google, has been evoking a tremendous digital disruption toward the libraries. Until 2016, Google had successfully scanned 30 million in 480 languages. Both libraries and librarians, as the most responsible party in providing quality information to their customers, should provide this extraordinary source as an alternative to meet the information needs of their communities, unfortunately, this tremendous potential has not been widely introduced yet. In order for this great blessing could be utilized by library users, librarians are recommended to instruct their users online searching skils for Gooogle Books database, in such way, information is obtained precisely